2009
DOI: 10.3109/00365590903413627
|View full text |Cite
|
Sign up to set email alerts
|

Posterior and anterior fixation of the urethra during robotic prostatectomy improves early continence rates

Abstract: The posterior and anterior fixation of the vesicourethral anastomosis during RRP results in an intact sphincteric mechanism, because no stretch is applied to the urethra, resulting in earlier continence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 11 publications
0
26
0
1
Order By: Relevance
“…In a randomised clinical trial, Jeong et al [23] observed a shorter time to social continence for their one-step posterior reconstruction (18 d) compared to no reconstruction (30 d). In two other randomised clinical trials, Hurtes et al [24] and Koliakos et al [25] found better early continence rates after combined posterior and anterior reconstructions compared to standard single-layer anastomosis. In the largest prospective study to date (803 patients), Coelho et al [26] observed a shorter interval to urinary continence recovery and, similar to our findings, no significant difference in long-term continence rates.…”
Section: Discussionmentioning
confidence: 94%
“…In a randomised clinical trial, Jeong et al [23] observed a shorter time to social continence for their one-step posterior reconstruction (18 d) compared to no reconstruction (30 d). In two other randomised clinical trials, Hurtes et al [24] and Koliakos et al [25] found better early continence rates after combined posterior and anterior reconstructions compared to standard single-layer anastomosis. In the largest prospective study to date (803 patients), Coelho et al [26] observed a shorter interval to urinary continence recovery and, similar to our findings, no significant difference in long-term continence rates.…”
Section: Discussionmentioning
confidence: 94%
“…When using a strict 0-pad definition, authors have reported 1 month continence rates varying between 26 and 72%, [14][15][16][17] while other studies reported rates varying between 65% and 85% for a 0-1 safety pad definition. [18][19][20] Comparatively, in our cohort, the continence rate 1 month after RARP was 44% using a strict 0-pad definition, and 63% using a 0-1 safety pad definition.…”
Section: Discussionmentioning
confidence: 96%
“…Buna karşın Koliakos ve Hurtes'in çalışmalarında total rekonstrüksiyon ile daha yüksek kontinans oranları bildirilmiştir (37,39). Tan ve ark.…”
Section: Posterior Ve Anterior Rekonstrüksiyonunclassified